Improved Bounds for Restricted Isometry Constants - Jiabing Ji; Jigen Peng (Discrete Dynamics in Nature and Society)
The purpose of this paper is to establish improved bounds for restricted isometry constants δk. Our results, to some extent, improve and extend the well-known bound (δk<0.307) in (Cai et al., 2010) to δk<0.308.